## How to solve the "Subscript indices must either be real positive integers or logicals." error.

### Naiara Tabanez (view profile)

on 11 Sep 2019
Latest activity Answered by Shunichi Kusano

### Shunichi Kusano (view profile)

on 11 Sep 2019
Hi, guys.
First of all, I am trying to solve a heat transfer problem with the finite volume method, but I don't know where am I failing in, and how to solve it.
Thank you all!
%unidimensional heat transfer
Ts=50;
i=6;
s=100;
T=zeros(i);
alfa=6.82*10^-6;
x=[1 2 3 4 5 6];
L=1;
dt=0.01;
for t=1:s
Tc=(2*Ts-T(1));
Tf=(2*Ts-T(6));
T(1)=alfa*dt((1/alfa*t*dt)*T(1)+(1/alfa*t*dt)*T(1)-(2/alfa*(L/6))*T(1)+(1/alfa*(L/6))*T(2)+(1/alfa*(L/6))*Tc);
T(2)=alfa*dt((1/alfa*t*dt)*T(2)+(1/alfa*t*dt)*T(2)-(2/alfa*(L/6))*T(2)+(1/alfa*(L/6))*T(3)+(1/alfa*(L/6))*T(1));
T(3)=alfa*dt((1/alfa*t*dt)*T(3)+(1/alfa*t*dt)*T(3)-(2/alfa*(L/6))*T(3)+(1/alfa*(L/6))*T(4)+(1/alfa*(L/6))*T(2));
T(4)=alfa*dt((1/alfa*t*dt)*T(4)+(1/alfa*t*dt)*T(4)-(2/alfa*(L/6))*T(4)+(1/alfa*(L/6))*T(5)+(1/alfa*(L/6))*T(3));
T(5)=alfa*dt((1/alfa*t*dt)*T(5)+(1/alfa*t*dt)*T(5)-(2/alfa*(L/6))*T(5)+(1/alfa*(L/6))*T(6)+(1/alfa*(L/6))*T(4));
T(6)=alfa*dt((1/alfa*t*dt)*T(6)+(1/alfa*t*dt)*T(6)-(2/alfa*(L/6))*T(6)+(1/alfa*(L/6))*Tf+(1/alfa*(L/6))*T(5));
end
plot(x,T);

### Shunichi Kusano (view profile)

on 11 Sep 2019

Hi Naiara,
The error occurs, since you use "dt" as an array, though it is a scalar. The problem is the first "dt" of each sentence in the following codes.
T(1)=alfa*dt((1/alfa*t*dt)*T(1)+(1/alfa*t*dt)*T(1)-(2/alfa*(L/6))*T(1)+(1/alfa*(L/6))*T(2)+(1/alfa*(L/6))*Tc);
T(2)=alfa*dt((1/alfa*t*dt)*T(2)+(1/alfa*t*dt)*T(2)-(2/alfa*(L/6))*T(2)+(1/alfa*(L/6))*T(3)+(1/alfa*(L/6))*T(1));
T(3)=alfa*dt((1/alfa*t*dt)*T(3)+(1/alfa*t*dt)*T(3)-(2/alfa*(L/6))*T(3)+(1/alfa*(L/6))*T(4)+(1/alfa*(L/6))*T(2));
T(4)=alfa*dt((1/alfa*t*dt)*T(4)+(1/alfa*t*dt)*T(4)-(2/alfa*(L/6))*T(4)+(1/alfa*(L/6))*T(5)+(1/alfa*(L/6))*T(3));
T(5)=alfa*dt((1/alfa*t*dt)*T(5)+(1/alfa*t*dt)*T(5)-(2/alfa*(L/6))*T(5)+(1/alfa*(L/6))*T(6)+(1/alfa*(L/6))*T(4));
T(6)=alfa*dt((1/alfa*t*dt)*T(6)+(1/alfa*t*dt)*T(6)-(2/alfa*(L/6))*T(6)+(1/alfa*(L/6))*Tf+(1/alfa*(L/6))*T(5));